RETRACTED: Review of methods and devices for determining the resistance to heat transfer under natural conditions - Zubarev K.P.; Alikhanova Z.R.; Zavarzin N.Yu.; Babich D.K. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001